Deformación neógena en el Antearco de Chiloé: reactivacion selectiva de estructuras extensionales - Echaurren Gonzalez, Andres (2017)
The forearc zone in the Andean subduction zone at ~42-44° S exhibits a particular configuration given by basins with a thick sedimentary infilling, a pronounced forearc high, and a west-vergent structure potentially related to the Liquiñe-Ofqui Fault Zone. Here, field and subsurface sedimentary units of late Oligocene - early Miocene age record the transition from an extensional to a contractional regime acting since middle Miocene times. New field and seismic data constrain this deformation as focused in the north of the segment, suggesting a differential contractional reactivation of the previous extensional structures. Causes of this compressive stage could be initially associated to the accretion of the Chiloé block that drifted in the previous extensional phase during the late Oligocene-early Miocene.